Service learning in higher education: a systematic literature review - Salam, Maimoona; Dayang Nurfatimah, Awang Iskandar; Ibrahim, D.H.A.; Farooq, M.S. (Springer Netherlands, 2019)
In the last few years, adoption of service learning in higher educational institutions has emerged as a modern teaching and learning strategy. This study is aimed to offer a systematic literature review of service learning implementation in higher education. There is a lack of research on the role of service learning in higher education sector. Moreover, a comprehensive systematic literature review of service learning in higher education is also overlooked in previous studies. Therefore, this study covers an in-depth systematic literature review, which reflects the utilisation approach and outcomes of service learning in higher education. By employing a rigorous exploratory approach, this study offers four major findings: (1) Acceptance and use of service learning in different academic disciplines, which covers a detailed discussion of up to what extent service learning pedagogy practice exists in each discipline. (2) Emerging issues regarding the integration of service learning in different academic disciplines. (3) Comparative analysis of previous service learning frameworks, which includes theoretical foundation, main findings and limitations of each framework. (4) Potential benefits of service learning for all participants. Service learning presents diverse benefits for all stakeholders; we identified the list of potential outcomes in the light of emerging service learning literature. These findings show that service learning is frequently employed in some academic disciplines, i.e. medical and nursing sciences; business and economics; computer science and information system; social studies; teacher education; linguistic and environmental disciplines. Moreover, comparison of previous service learning frameworks revealed that most of them are subject-oriented, specifically focused on institutionalising and practical aspects. © 2019, Education Research Institute, Seoul National University, Seoul, Korea.